Comment on "Evaluation of Manual and Two-Rotary NiTi Retreatment Systems in Removing Gutta-Percha Obturated with Two Root Canal Sealers". (27th May 2013) - Dixit, Seema K.; Arora, Varun; Loomba, Kapil; Dixit, Ashutosh; Gaunkar, Ridhima Birmani; Agarwal, Bhaskar; Misra, Alok; Gupta, Narendra kumar
Abstract : Proper research design, appropriate evaluation and measurement methods, use of correct statistical tests, interpretation, and inference are the essentials without which any scientific research reporting is incomplete and does not serve its proposed purpose. In this communication, some common flaws in research designing, evaluation, analysis, and inference have been explained using a published article as a reference. The purpose of the paper is to help the scientific community recognize the significance of proper research designing and planning in order to achieve the results which are worthwhile.